Estudio para la implementación de un laboratorio de meteorología aeronáutica con equipos reincorporados como herramienta de enseñanza práctica - Ingrid Tatiana Sierra Giraldo; Edgar Leonardo Gómez Gómez; Jonathan Fernando Varón Castro (Ciencia y Poder Aéreo, 2019)
This article presents the results of a research project whose objective is to evaluate the implementation of a meteorological laboratory with reused equipment in the facilities of the Center for Aeronautical Studies (CEA, by Its Spanish Acronym), in order to use it as a tool that reinforces the learning process of students who take academic programs related to meteorological topics. This is possible through the teaching experience offered by a workstation implemented with reincorporated equipment, that simulates the real working conditions of a weather station operator, which will collect meteorological data in real-time through a network of specialized sensors, that in this case are also reused. As a development methodology, the operating conditions of all equipment deactivated in different locations throughout the country and in the old National Analysis and Forecast Center are evaluated, due to the transfer of this service to the Center for Aeronautical Management of Colombia (CGAC, by Its Spanish Acronym). The possibility of locating them in CEA's physical facilities is analyzed, thus obtaining the data that indicate the viability of implementing this laboratory, laying the bases for its development. It is expected that this laboratory will significantly benefit the training processes of personnel who provide Air Navigation Services, thus contributing to the fulfillment of the functions of the CEA and therefore, the personnel who are trained there and its institutions.